2009 IEEE 10th Workshop on Signal Processing Advances in Wireless Communications 2009
DOI: 10.1109/spawc.2009.5161785
|View full text |Cite
|
Sign up to set email alerts
|

An SNR balancing approach to two-way relaying

Abstract: We consider a relay network which consists of two transceivers and r relay nodes. Assuming that the transceivers and the relays are all equipped with single antennas, we devise a two-way amplify-andphase-adjust relaying scheme. In this scheme, each relay multiplies its received signal by a complex weight and transmits the so-obtained signal thereby participating in a distributed beamforming process. We deploy an SNR balancing technique where the smallest of the two transceiver SNRs is maximized while the total… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
6
0

Year Published

2009
2009
2015
2015

Publication Types

Select...
4
1

Relationship

2
3

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 8 publications
0
6
0
Order By: Relevance
“…As the optimal beamforming vector is unique(i.e., w(p o As a simple suboptimal solution, one can choose p o 1 =P /4. In[1], the authors have shown thatp o 1 + p o 2 =P /2, we obtain that p o 2 = p o 1 =P /4.Although this solution is suboptimal, if different diagonal entries of D1 and D2 are drawn from the same pdf, the choice of p o 1 = p o 2 =P /4 can be close to the optimal solution thus alleviating the need for solving (20). We will evaluate the performance of both (optimal and suboptimal) solutions via numerical examples.…”
mentioning
confidence: 79%
See 4 more Smart Citations
“…As the optimal beamforming vector is unique(i.e., w(p o As a simple suboptimal solution, one can choose p o 1 =P /4. In[1], the authors have shown thatp o 1 + p o 2 =P /2, we obtain that p o 2 = p o 1 =P /4.Although this solution is suboptimal, if different diagonal entries of D1 and D2 are drawn from the same pdf, the choice of p o 1 = p o 2 =P /4 can be close to the optimal solution thus alleviating the need for solving (20). We will evaluate the performance of both (optimal and suboptimal) solutions via numerical examples.…”
mentioning
confidence: 79%
“…It is shown in [1] that the maximum is achieved when SNR1 = SNR2 holds true, and hence, the optimization problem (6) is equivalent to…”
Section: Preliminariesmentioning
confidence: 99%
See 3 more Smart Citations